Flow Regulation Characteristics of Active Flow-Regulating Vanes in U-Shaped Bends - LI Lin, ZHANG Jing-kai, ZHANG Lu-guo, CHI Miao-miao, XIAO Yu-lei (长江科学院院报, 2025)
[Objective] To address the issue that conventional river regulation structures struggle to dynamically adapt to the highly variable characteristics of natural rivers, this study develops an innovative active flow-regulating vane system. [Methods] The system combined a vertically adjustable and rotatable vane structure with a remote intelligent control module. It allowed real-time monitoring and dynamic adjustment of flow parameters, thereby overcoming the limitations of traditional fixed structures such as spur dikes and deflector vanes. To investigate its applicability in curved river channels, the flow-regulating vanes were arranged in a 180°U-shaped bend model. The verified RNG k-ε turbulence model and VOF method were used to conduct numerical simulations of the bend’s flow field characteristics before and after the vane installation. The impact of the flow-regulating vanes on the hydrodynamic structure of the bend was analyzed. [Results] 1) Numerical results showed that when the top of the flow-regulating vanes was flush with the free water surface (at a flow rate of 7.9 L/s), the longitudinal velocity near the convex bank region increased by 21.67% compared to the original bend, while the maximum transverse velocity in the central region decreased by 70.33%, effectively weakening the transverse circulation. When the vanes were submerged to 0.3 times the water depth (at a flow rate of 15.8 L/s), the longitudinal velocity still increased by 13.64%, and the transverse velocity decreased by 37.63%. 2) Analysis of the flow field structure revealed that the vanes could split the original single clockwise vortex circulation structure within the bend into two vortices rotating in the same direction, which reduced the flow’s kinetic energy, lowered the circulation velocity, and decreased transverse sediment transport. 3) The distribution of bed shear stress showed that, after the installation of the flow-regulating vanes, the bed shear stress within the bend was uniformly distributed along the convex bank side, which helped alleviate sedimentation on the convex bank while avoiding concentrated scouring. Moreover, the suspended design of the vanes reduced flow obstruction at the bend bottom, solving the sedimentation problem caused by decreased flow velocities around traditional structures fixed to the riverbed, making it a viable option for flow regulation in hardened bend channels.